Satellite a-dinsar monitoring of the Vittoriano monument (Rome, Italy): implications for heritage preservation - Bozzano, Francesca; Ciampi, Paolo; Del Monte, Maurizio; Innocca, Federico; Luberti, Gian Marco; Mazzanti, Paolo; Rivellino, Stefano; Rompato, Matteo; Scancella, Stefano; Scarascia Mugnozza, Gabriele (Italian journal of engineering geology and environment, 2020)
<span data-sheets-value=""1":2,"2":"The “Vittoriano” monument, dedicated to king Vittorio Emanuele II, is one of the most famous cultural heritage landmarks in Rome (Italy), even because it hosts the Tomb of the unknown soldier, monument o the Italian fallen in wars. It was designed by the architect Giuseppe Sacconi at the end of 19th century and since the beginning of its construction, it has been affected by cracks and deformations. In the last years, such phenomena have become more evident, especially on the western side of the building. With the aim of understanding the causes of the deformation process and making a diagnosis of the oil-structure interaction of the Monument, a specific project has been undertaken between CERI Sapienza and the Lazio Museum Network. Satellite ADInSAR was performed to infer the recent deformational history of the main parts of the monument, by using medium and high-resolution SAR images acquired in double orbital geometry (ascending and descending) and covering the last two decades. Through the support of selected geological and lithotechnical data it was possible to interpret the deformational dynamics of the Vittoriano. The overall investigations allowed to better define the volume and the structures that have been involved in the deformation mechanisms, which is currently driving the overall process, in order to address effective mitigation measures. They are capable of backward analysing the deformational process, reconstructing the evolution of a phenomenon and above all capable of easily investigating large areas."" data-sheets-userformat=""2":13249,"3":"1":0,"9":0,"10":1,"11":3,"12":0,"15":"Arial","16":8">The “Vittoriano” monument, dedicated to king Vittorio Emanuele II, is one of the most famous cultural heritage landmarks in Rome (Italy), even because it hosts the Tomb of the unknown soldier, monument o the Italian fallen in wars. It was designed by the architect Giuseppe Sacconi at the end of 19th century and since the beginning of its construction, it has been affected by cracks and deformations. In the last years, such phenomena have become more evident, especially on the western side of the building. With the aim of understanding the causes of the deformation process and making a diagnosis of the oil-structure interaction of the Monument, a specific project has been undertaken between CERI Sapienza and the Lazio Museum Network. Satellite ADInSAR was performed to infer the recent deformational history of the main parts of the monument, by using medium and high-resolution SAR images acquired in double orbital geometry (ascending and descending) and covering the last two decades. Through the support of selected geological and lithotechnical data it was possible to interpret the deformational dynamics of the Vittoriano. The overall investigations allowed to better define the volume and the structures that have been involved in the deformation mechanisms, which is currently driving the overall process, in order to address effective mitigation measures. They are capable of backward analysing the deformational process, reconstructing the evolution of a phenomenon and above all capable of easily investigating large areas.